Engaging under- and/or never-engaged populations in health services: A systematic review - Lesley Moody; Erica Bridge; Vidhi Thakkar; Naomi Peek; Tanvi Patel; Suman Dhanju; Simron Singh (The Beryl Institute, 2019)
Patient engagement is a mechanism used to facilitate person-centred care, however, has not been realized in all patient populations. Often, many marginalized populations still remain under- and/or never-engaged. The purpose of this systematic review was to: 1) identify methods or interventions that have been used to engage under- and/or never-engaged populations in health services and 2) identify outcomes that are associated with engaging under- and/or never-engaged populations in health services. A comprehensive search using the Ovid MEDLINE, EMBASE and CINAHL databases was conducted to examine literature between January 2002 and January 2015. Twenty-nine studies met the inclusion criteria. Data was extracted from these studies and findings are synthesized based on discrete themes that map to the research objectives. The majority of studies were quantitative, repeated-measures designs and concentrated in the United States. Hispanic and Latino/a populations were most frequently included in these studies. The main methods of recruitment included: 1) referral from a healthcare provider, 2) patient self-referral after seeing advertisements on mass media or targeted media, 3) directly approached by researcher in-person or telephone, and 4) administrative databases. Interventions occurred primarily at the individual-level, however some system-level interventions were identified. Five main outcomes resulted from the interventions, including: 1) behavioural change, 2) physiological, 3) psychosocial, 4) system and 5) process. Finally, culture-specific components were embedded in the interventions, both as surface and deep structures. This study provides future direction for patient engagement related projects, as it relates to under-and never-engaged population in healthcare. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.